Kualitas Hidup Lansia di Desa Subamia Wilayah Kerja Puskesmas Tabanan II tahun 2022 - Panca Tri Pramana; Luh Gede Pradnyawati; Made Indra Wijaya (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
The elderly are considered a group of people over the age of 60 who are susceptible to age-related diseases. The number of elderly in the world is predicted to increase from 962 million elderly in 2017 to 1.4 billion elderly in 2030, 2.1 billion elderly in 2050 and by 2100 to reach 3.1 billion elderly. A person in old age will show signs of decline in physical, mental and social aspects. As a result of the problems that occur, an elderly person must be considered for their quality of life. A high quality of life indicates that a person reaches perfection at the end of his life, while a low quality of life can lead to despair in the elderly. The purpose of this study was to measure the level of quality of life of the elderly in Subamia Village in 2022. This study was conducted in November 2022. Sampling was conducted in Subamia Village, Tabanan Regency, Bali Province. The research method used is a quantitative descriptive method with a research design, namely a cross-sectional design. The data collection technique used consecutive sampling with a total of 80 respondents. Data collection was carried out during elderly posyandu activities using WHOQOL-BREFF with interview-based questionnaire techniques. Data were collected sequentially until the minimum number of samples was reached. Data analysis using univariate analysis.The results of the research on the quality of life of the elderly in Subamia Village based on physical obtained moderate criteria (65%), based on psychological obtained moderate criteria (50%), based on social relations obtained moderate criteria (63.7%), and based on environmental obtained moderate criteria (63.7%).